Efficacy of Entomopathogens, Botanical and New Generation Insecticides Against Papaya Mealybug - Islam, A; Haque, MA; Das, G; Khan, AA; Topu, MAA; Rahman, MS; Hasan, MJ; Mollah, MLR; Roknuzzaman, M (Bangladesh Journal of Nuclear Agriculture, 2023)
The papaya mealybug is an invasive polyphagus pest species causing several economic damages to a wide range of agricultural crop. Five new generation insecticides of different groups, one botanical and one entomopathogenic fungus (Beauveria bassiana) were evaluated in laboratory for their effectiveness in reducing mealybug incidence on papaya. The present study was conducted to evaluate the toxic effect of different insecticides at different concentration against P.marginatus. Among the 7 insecticides, Imixam 70 WDG (Imidacloprid+Thiamethoxam) was the most effective insecticide followed by Ravjum 14.5 SC (Indoxacarb), Saka 25 SC (Abamectin 5% +Spirodiclofen 20%), Imixan and Biotrin 0.5% (Matrin), Tundra 20 SP (Acetameprid), Antario (Bacillus thuringiensis+Abamectin) and Beauveria bassiana, respectively.All the selected insecticides provided their highest efficacy at their maximum doses as well as within 7-9 DAT, among them two new generation insecticides e.g. Saka 25 SC (Abamectin 5% +Spirodiclofen 20%) @ 1.0 ml/L, Ravjum 14.5 SC (Indoxacarb) @ 1.0 ml/L and the botanical insecticide Biotrin 0.5% upto 7 DAT would be effective in controlling papaya mealybug considering the efficacy. To confirmation of the results, need to be tested under field condition. Bangladesh J. Nuclear Agric, 37(2): 81-88, 2023